Combination of Aloe Vera and Chocolate to Reduce The Number of The Colony of Staphylococcus Aureus - Edy Suwandi; Ari Nuswantoro; Sugito Sugito (POLTEKKES KEMENKES PONTIANAK, 2022)
Aloe vera (AV) and chocolate are good examples of functional foods because they contain prebiotics that can help the host defend itself against harmful bacterial infections such as Staphylococcus aureus. Many studies have used AV or chocolate alone to help fight infection, but not much is known about using both together. This study aims to count the number of colonies of S. aureus infected on mice’s skin (Mus musculus) after being given AV and cocoa in certain doses per kilogram of body weight. A total of 35 healthy male mice were infected with S. aureus in the superficial area of ​​the nape of the skin. After that, they were divided into seven groups, each consisting of 5 mice, and given the following treatments: given 50 mg/kg BW AV (group A), 50 mg/kg BW brown (B), 50 mg/kg BW combination of AV and chocolate (C), given 75 mg/kg BW AV (D), given 75 mg/kg BW brown (E), given 75 mg/kg BW combination of AV and chocolate (F), and control (without prebiotic administration), K). Mice that were given 75 mg/kg BW AV/chocolate/AV+chocolate had a better ability to reduce the number of bacteria than those that were given 50 mg/kg BW AV/chocolate/AV+chocolate. In addition, rats that were given AV and chocolate together had a better ability to reduce the number of bacteria than those that were given either only AV or chocolate alone. Prebiotics are both found in AV and chocolate but with different substances. This causes mice given a combination of prebiotics to be considered better than those given only one type of prebiotic source.